INTERNAL AUDIT: THE APPLICATION OF RISK MANAGEMENT AND ELECTRONIC CHANNELS INTERNET BANKING THROUGH THE AUDIT MANAGEMENT SYSTEM IN THE QUALITY OF FINTECH GOVERNANCE IN BANKING INDUSTRY - Suryaningsih, Ika Barokah; Putrihandani, Yuani; Nugraha, Kristian Suhartadi Widi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2018)
This article aims to prove the role of internal auditors in providing added value in improving the quality of governance in the banking sector. The role of information technology in the banking industry sector is very dominant in service operations. This condition requires banks to apply their prudential principles by guaranteeing the implementation of risk management and electronic channel internet banking through audit management control systems. This study used an explanatory research approach with census data collection methods. The object of this study was the internal auditors of a branch office of one of the national private banks in Jember. The data of this study were the results of the response of 41 internal auditors of various branches and sub-branches in Jember Regency and supported by a literature review of the annual report of banks’ internal audit performance with a path analysis data processing tool. The results of the study showed that the application of risk management and electronic channel internet banking had an effect on the audit management system and the quality of financial technology governance.